Roads and urban areas as physiological stressors of spiny-tailed lizards, Uromastyx acanthinura. (November 2019) - Kechnebbou, Marwa; Martín, José; Chammem, Mohsen; Arregui, Lucía; Nouira, Said
Abstract: Disturbances caused by roads or urbanization can have a significant impact on wildlife populations. However, it remains unclear whether these human activities can be stressors for wild populations of reptiles. We analyzed and compared plasma corticosterone and fecal corticosterone metabolites in male and female spiny tailed lizards ( Uromastyx acanthinura ) that were found at different distances from roads and urban areas in Tunisia (N. Africa). Levels of plasma corticosterone and fecal corticosterone metabolites of the same individuals measured with an enzyme immunoassay kit were highly and significantly correlated. This indicated that non-invasive measures of stress levels are equally useful for these types of studies. Males had higher plasma corticosterone than females, and these levels were higher in autumn than in summer and spring in both sexes. Moreover, levels of corticosterone in plasma and corticosterone metabolites in feces were significantly higher when the capture site was closer to roads or urban areas. These results suggest that the alteration of the natural habitat and the disruption caused by road traffic increase stress hormone levels in U. acanthinura lizards. Understanding how free-living animals are influenced by human perturbations could help direction and involvement of conservation strategies for endangered species. Highlights: Human activities can be stressors for wild populations of reptiles. Corticosterone levels were higher in lizards living closer to roads or urban areas. Levels of stress measured in blood or feces were highly correlated. Habitat alteration and road traffic increase stress in Uromastyx acanthinura lizards.